Yet another case of nordic exceptionalism?: extending existing evidence for a causal relationship between institutional and social trust to the Netherlands and Switzerland - Seifert, Nico (Social indicators research, 2018)
Social trust has typically been considered a deep-seated, thus stable, disposition. However, in accordance with institutional theory, a recent analysis applying fixed effects regressions provides strong evidence for a causal influence of trust in state institutions on social trust in Denmark, indicating that trust in other people might be malleable through the quality of state institutions. However, it is still unclear whether this finding can be generalised beyond the setting of Danish or Nordic exceptionalism—a social environment highly conducive to trust. Against this backdrop, the purpose of this study is to test the institutional theory in two other European countries: the Netherlands and Switzerland. Drawing on the LISS panel and the Swiss Household Panel, each with different strengths and weaknesses, the results provide further support for the idea that trust in the majority of other people is shaped by the trustworthiness of state institutions in Western societies.